Fish species composition recorded in the Red river basin within the territory of the Thai Binh and Nam Dinh provinces, northern Vietnam - Duc, Nguyen Huu; Hong Ninh, Pham Thi; Mai Huong, Ngo Thi (Academia Journal of Biology, 2014)
Based on 924 collected fish specimens of ten field surveys from 9 locations in the Red River valley within the territory of the Thai Binh and Nam Dinh provinces during December 2010 to August 2012, the total of 193 species of fish species belonging to 131 genera, 53 families and 13 orders have been recorded. There are 130 species, 61 genera, 11 families and 1 order recorded for the first time for the this fish fauna. Ađitionally, there are 108 species, 82 genera and 43 families reported in the previous survey are not seen. To date, the fish number of the research area is totally 301 species belonging to 178 genera, 70 families and 18 orders recorded. Of the total 18 orders, Perciformes is the most abundant of families level with 48.62%, the most diverse in genera with 53.08% and species level with 12.87%. In the the Red River valley within the territory of the Thai Binh and Nam Dinh provinces, seven species were revealed as listed in the Red Data Book of Vietnam, one species of CR level: four-eyed sleeper Four-eyed sleeper (B. sinensis); two species of EN level: Chinese gizzard shad (C. thrissa) and Blotched snakehead (C. maculata) and four species of VU level: Greater pipefish (S. acus), Ladyfish (E. saurus), Dotted gizzard shad (K. punctatus) and Bloch's gizzard shad (N. nasus). There are 116 species wide salt and 183 species of narrow salt.